2015
DOI: 10.1016/j.jplph.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxycinnamic acids and UV-B depletion: Profiling and biosynthetic gene expression in flesh and peel of wild-type and hp-1

Abstract: Hydroxycinnamic acids (HCAs) are phenolic compounds widely found in most plant families. Aim of the present work was to investigate their accumulation and biosynthetic gene expression in presence or absence of UV-B radiation in tomato fruits of wild-type and hp-1, a mutant characterized by exaggerated photoresponsiveness and increased fruit pigmentation. Gene expression and HCAs content were higher in hp-1 than in wild type peel and UV-B depletion determined a decrease in HCAs accumulation in wild-type and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…These results may suggest that preferential accumulation of CA and FA in the peel is a part of acclimation response to direct exposure to solar radiation, while in the flesh other factors may influence the composition of HCAs. Similarly to our results for 2013 and 2014, Calvenzani et al (2015) reported that total concentration of HCAs in fully ripe tomato fruits was higher under ambient UV-B than in UV-B shielded fruits.…”
Section: Phenolic Compounds In Tomato Fruitssupporting
confidence: 91%
“…These results may suggest that preferential accumulation of CA and FA in the peel is a part of acclimation response to direct exposure to solar radiation, while in the flesh other factors may influence the composition of HCAs. Similarly to our results for 2013 and 2014, Calvenzani et al (2015) reported that total concentration of HCAs in fully ripe tomato fruits was higher under ambient UV-B than in UV-B shielded fruits.…”
Section: Phenolic Compounds In Tomato Fruitssupporting
confidence: 91%
“…In addition, UV Resistance Locus8 (UVR8) initiates the stress signaling response by receiving UV-B light [ 2 , 7 , 9 , 10 ]. Among UV-B stress responses, an important change in terms of secondary metabolites is the accumulation of phenolic compounds, such as flavonoids, anthocyanins, and hydroxycinnamic acids (HCAs), that function as sunscreens in vacuoles of epidermal cells to protect important subcellular components from UV-B light [ 11 , 12 , 13 ]. However, plant responses to UV-B light depend on its energy level, duration, and peak wavelength and on the plant species, varieties, and growth stages [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic acids are responsible for the astringent taste of tomato fruits and consist mainly of gallic, chlorogenic, and ferulic acids ( Moco et al, 2007 ). Hydroxycinnamates, due to their antioxidant capacity, have important beneficial health effects: they can limit LDL (low-density lipid) oxidation, prevent carcinogenesis and are potential therapeutic agents for neurodegenerative diseases, such as Alzheimer and Parkinson and for the prevention of cardiovascular disease and diabetes ( Niggeweg et al, 2004 ; Calvenzani et al, 2015 ; Tohge et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%